Therapeutic Potential of Extracellular Vesicles for the Treatment of Nerve Disorders - Galieva, Luisa R.; James, Victoria; Mukhamedshina, Yana O.; Rizvanov, Albert A. (Frontiers in Neuroscience, 2019)
The use of extracellular vesicles (EVs) as cell free therapy is a promising approach to stimulate tissue regeneration including that of the nervous system. EVs transfer bioactive proteins and lipids, RNA and microRNAs, which play a relevant role in EV-mediated intercellular communication. The immunomodulatory, anti-inflammatory and neuroprotective effects of mesenchymal stem cells-derived EVs have been well studied, knowledge of this paracrine mechanism and the availability of these cells, positions mesenchymal stem cells as a potential source of EVs for cell free therapy for a variety of regenerative and nervous system disorders. In this review, we focus on the immunomodulatory and neuroprotective effects of stem cells-derived EVs within in vitro and in vivo models of nerve disorders.